2006
DOI: 10.1016/j.neuron.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Promote Myelination in Response to Electrical Impulses

Abstract: Myelin, the insulating layers of membrane wrapped around axons by oligodendrocytes, is essential for normal impulse conduction. It forms during late stages of fetal development but continues into early adult life. Myelination correlates with cognitive development and can be regulated by impulse activity through unknown molecular mechanisms. Astrocytes do not form myelin, but these nonneuronal cells can promote myelination in ways that are not understood. Here, we identify a link between myelination, astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
521
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 590 publications
(545 citation statements)
references
References 34 publications
(36 reference statements)
14
521
0
4
Order By: Relevance
“…Previously we determined that the synthesis and secretion of LIF from astrocytes can be regulated by electrical impulses in dorsal root ganglion axons to stimulate myelination by oligodendrocytes (Ishibashi et al, 2006). The hypothesis that a similar molecular mechanism could regulate differentiation of hippocampal GFAP-positive astrocytes in an activitydependent manner was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously we determined that the synthesis and secretion of LIF from astrocytes can be regulated by electrical impulses in dorsal root ganglion axons to stimulate myelination by oligodendrocytes (Ishibashi et al, 2006). The hypothesis that a similar molecular mechanism could regulate differentiation of hippocampal GFAP-positive astrocytes in an activitydependent manner was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was assayed in duplicate for LIF content using a Quantikine LIF ELISA assay (R&D Systems, Minneapolis, MN) on a Victor Wallac microtiter plate reader as previously described (Ishibashi et al, 2006).…”
Section: Lif Elisamentioning
confidence: 99%
See 1 more Smart Citation
“…They depend on genetic and environmental factors, such as the level of electrical activity of an axon [23,24] and on experience [25]. Previous studies showed significant pruning in the corpus callosum during development of rhesus monkeys resulting in 3.5 times less axons in adults than at birth [26], whereas the remaining axons with high electrical activity get thicker myelin sheet [27]. The co-occurring myelination and pruning with other changes in the white matter microstructure during childhood was found to result in a net increase of FA in many brain regions [18].…”
Section: Discussionmentioning
confidence: 99%
“…This may in part reflect the activity-evoked release of ATP and adenosine (Stevens et al, 2002;Ishibashi et al, 2006;Hamilton et al, 2008), but the presence of glutamatergic and GABAergic synapses onto OPCs (Bergles et al, 2000;Lin and Bergles, 2004;Jabs et al, 2005;Kukley et al, 2007;Ziskin et al, 2007;Káradóttir et al, 2005Káradóttir et al, , 2008 suggests that synaptic contacts from unmyelinated axons to OPCs (and possibly production of action potentials in the OPCs) may play a key role in initiating myelination. Since synapses are made predominantly onto the Na þ channel expressing OPCs (Káradóttir et al, 2008), which can sense neural activity as a synaptic input, these cells might carry out a different type of myelination programme, that is regulated differently, from the ohmic OPCs that lack synaptic input and so do not sense neuronal activity in this way.…”
Section: T W O T Y P E S O F O P C T W O T Y P E S O F M Y E L I Nmentioning
confidence: 99%